AKTUALISASI PEDOMAN HIDUP ISLAMI WARGA MUHAMMADIYAH (PHIWM) DALAM MEMBENTUK KESALEHAN INDIVIDUAL DAN SOSIAL DI ERA KONTEMPORER - Nadya Unasyah Arifin; Auliani Nisa; Dahlan Lama Bawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe and analyze the urgency of the Islamic Living Guidelines for Muhammadiyah Citizens (PHIWM) as a normative and practical guide in facing the challenges of moral degradation in the modern era. PHIWM is a set of values and norms derived from the Qur'an and As-Sunnah to serve as a pattern for the behavior of Muhammadiyah members. The method used in this research is qualitative with a library research approach. The primary data source is the decision of the 44th Muhammadiyah Congress in 2000 regarding PHIWM. The results show that PHIWM covers broad dimensions of life, ranging from personal life, family, community, organization, to nation and state life. The actualization of PHIWM values is highly relevant for shaping the character of Muhammadiyah members who possess a balance between individual piety (habluminallah) and social piety (habluminannas), as well as serving as a solution to the crisis of exemplary leadership in society.